Relationship Between Reproductive Health Knowledge and Personal Hygiene During The Menstrual Period - Gina Fitriyah; Sriyatin S (Journal of Maternity Care and Reproductive Health, 2018)
Reproductive health issues are threatening adolescents,including when they having menstrual period. It may because of  the usage of pads in a long time, or inappropriate of underwear.  WHO (2006) argued that the problems of reproductive health among women remained high (33%). This study aimed to analyze the relationship of Reproductive Health Knowledge with Personal Hygiene behavior in the menstrual period.This study was a descriptive correlation with the approach of cross-sectional. The sampling technique was the proportionate stratified random sampling. The samples were 64 respondents. The data were analysed using univariate and bivariate analysis. The result of the study found that the understanding of reproductive health was low category (46,9%), moderate (34,4%), and high (18,8%), meanwhile the personal hygiene when having menstruation in a negative category (53,1%) and positive (46,9%). There were a significant relationship between reproductive health knowledge and personal hygiene during the menstural period (P value 0,82). The researcher expected that the respondents should find more information about reproductive health with the problems and do the personal hygiene appropriately in the menstrual period. Keywords: Reproductive health, knowledge, Personal hygieneMenstruation